2012
DOI: 10.1111/j.1365-2133.2012.10885.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression profile of cornified envelope structural proteins and keratinocyte differentiation-regulating proteins during skin barrier repair

Abstract: Skin barrier disruption induces a temporary barrier repair response composed of increased expression of several cornification-related proteins, and decreased expression of some structural and desquamation-related proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
66
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 52 publications
7
66
0
Order By: Relevance
“…Thus, they are considered a marker of the aberrant differentiation and proliferation of keratinocytes. It has been reported that SPRR protein was up-regulated following skin barrier disruption in the lesions of atopic dermatitis and psoriatic skin [40,41,42]. KLK6 is involved in the proteolysis of corneodesmosome, which cleaves desmoglein 1 [43].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, they are considered a marker of the aberrant differentiation and proliferation of keratinocytes. It has been reported that SPRR protein was up-regulated following skin barrier disruption in the lesions of atopic dermatitis and psoriatic skin [40,41,42]. KLK6 is involved in the proteolysis of corneodesmosome, which cleaves desmoglein 1 [43].…”
Section: Discussionmentioning
confidence: 99%
“…All of these biological functions are important for tissue growth, maintaining epithelial barrier integrity, and downregulating the inflammatory response. For example, cornifin B, cornulin, desmoglein 3,and cystatins are components of the epithelium that are important for generating and maintaining a cohesive keratinocyte barrier that is both flexible and yet impermeable (33)(34)(35)(36). Although serine protease inhibitors (serpins) aid in wound healing, epithelial damage repair, and the inhibition of inflammatory proteases, all of these functions contribute to a healthy, adherent, defensive barrier (37)(38)(39).…”
Section: Participant Characteristicsmentioning
confidence: 99%
“…However, impaired skin barrier function has also been shown in AD patients without FLG mutations [18] . Recently, the altered expression of genes encoding small proline-rich proteins and the LCE-like proline-rich 1 protein (LELP1) in the skin of AD patients has been documented [19,20] .…”
mentioning
confidence: 99%